The German health care Innovation Fund – An incentive for innovations to promote the integration of health care. Issue 8 (14th October 2020) - Berghöfer, Anne; Göckler, Denes G.; Sydow, Jörg; Auschra, Carolin; Wessel, Lauri; Gersch, Martin
Abstract : Purpose: Many health systems face challenges such as rising costs and lacking quality, both of which can be addressed by improving the integration of different health care sectors and professions. The purpose of this viewpoint is to present the German health care Innovation Fund (IF) initiated by the Federal Government to support the development and diffusion of integrated health care. Design/methodology/approach: This article describes the design and rationale of the IF in detail and provides first insights into its limitations, acceptance and implementation by relevant stakeholders. Findings: In its first period, the IF offered € 1.2 billion as start-up funding for model implementation and evaluation over a period of four years (2016–2019). This period was recently extended to a second round until 2024, offering € 200 million a year as from 2020. The IF is triggering the support of relevant insurers for the development of new integrated care models. In addition, strict evaluation requirements have led to a large number of health service research projects which assess structural and process improvements and thus enable evidence-based policy decisions. Originality/value: This article is the first of its kind to present the German IF to the international readership. The IF is a political initiative through which to foster innovations and promote integrated health care.